A mini-review on the emerging role of nanotechnology in revolutionizing orthopedic surgery: challenges and the road ahead - Deng, Yongjun; Zhou, Chao; Fu, Lifeng; Huang, Xiaogang; Liu, Zunyong; Zhao, Jiayi; Liang, Wenqing; Shao, Haiyan (Frontiers in Bioengineering and Biotechnology, 2023)
An emerging application of nanotechnology in medicine currently being developed involves employing nanoparticles to deliver drugs, heat, light, or other substances to specific types of cells (such as cancer cells). As most biological molecules exist and function at the nanoscale, engineering and manipulating matter at the molecular level has many advantages in the field of medicine (nanomedicine). Although encouraging, it remains unclear how much of this will ultimately result in improved patient care. In surgical specialties, clinically relevant nanotechnology applications include the creation of surgical instruments, suture materials, imaging, targeted drug therapy, visualization methods, and wound healing techniques. Burn lesion and scar management is an essential nanotechnology application. Prevention, diagnosis, and treatment of numerous orthopedic conditions are crucial technological aspects for patients' functional recovery. Orthopedic surgery is a specialty that deals with the diagnosis and treatment of musculoskeletal disorders. In recent years, the field of orthopedics has been revolutionized by the advent of nanotechnology. Using biomaterials comprised of nanoparticles and structures, it is possible to substantially enhance the efficacy of such interactions through nanoscale material modifications. This serves as the foundation for the majority of orthopedic nanotechnology applications. In orthopedic surgery, nanotechnology has been applied to improve surgical outcomes, enhance bone healing, and reduce complications associated with orthopedic procedures. This mini-review summarizes the present state of nanotechnology in orthopedic surgery, including its applications as well as possible future directions.